Factors Stimulating Internationalisation of Firms: An Attempted Holistic Synthesis - Magdalena Belniak (Entrepreneurial Business and Economics Review)
Objective: The main goal of this paper is the critical and synthetic analysis of internationalisation process factors, with reference to business management. It presents a systematic review of the most important relational ideas in regard to factors of firm-level internationalisation.